Evaluating differences in community-engaged learning and service-learning via the context, input, process, and product model - Nguyen, Jonathan J.; Condry, Danielle L. Jessen (Frontiers in Education, 2023)
Service-learning (SL) and community-engaged learning (CEL) are high-impact practices whose ideological foundations are built upon ideas pioneered by philosophers such as John Dewey and William James. Given that one methodology (CEL) directly branched from the other (SL), these practices are expected to have fundamental underpinnings that differentially influence how projects within these practices are carried out. Stufflebeam and Shinkfield's Context, Input, Process, and Product (CIPP) model for evaluation was applied to assess these two high-impact practices. This narrative review has two goals: 1) discuss the usage of the CIPP model to evaluate established SL and CEL projects, and 2) assess any differences in evaluation garnered from CIPP model usage that may have stemmed from nuances in SL and CEL ideology. Literature covering either practice had shown, in some cases, to be inconsistent with how the implementation and guiding principles of such projects matched the terminology used by project organizers. This discrepancy has implications for how these projects are carried out and evaluated in the future.